Titanium Dioxide Advances and Applications - Muhammad Ali, Hafiz (IntechOpen, 2022)
This book presents a comprehensive overview of titanium dioxide, including recent advances and applications. It focuses on the compound's uses in environmental remediation, photocatalytic materials, rechargeable lithium-ion batteries, thin films, energy storage, semiconductors, and much more. This volume is a useful resource for researchers, scientists, engineers, and students.